Identification of specific genes as molecular markers for rapid and accurate detection of oil-tea Camellia anthracnose pathogen Colletotrichum fructicola in China - Cao, Lingxue; Shi, Kailin; Liu, Yongyi; Xie, Xiaonan; Sun, Xizhe; Dong, Wentong; Wang, Congya; Ma, Lisong (Frontiers in Microbiology, 2024)
Camellia anthracnose is caused by multiple Colletotrichum species, resulting in severe yield losses of oil-tea Camellia. Colletotrichum fructicola is one of the major anthracnose pathogens of oil-tea Camellia worldwide. However, developing unique molecular markers for the rapid and accurate detection of Colletotrichum fructicola from diverse Colletotrichum species, as well as early monitoring and effective control of the disease, remains largely unexplored. In this study, Colletotrichum fructicola-specific molecular markers were developed for rapid and accurate detection of C. fructicola among Camellia anthracnose causing fungal pathogens. C. fructicola-specific genes were obtained using a BLAST search of the sequences of predicted genes in C. fructicola against the genome sequences of Colletotrichum fungal pathogens. Using DNA-based conventional and quantitative PCR, three C. fructicola-specific genes with the ability to distinguish C. fructicola from other oil-tea Camellia anthracnose-related Colletotrichum species, including Colletotrichum camelliae, Colletotrichum gloeosporioides, and Colletotrichum siamense, and oil-tea Camellia fungal pathogens belonging to the genus Neopestalotiopsis, Pestalotiopsis and Alternaria, were validated as molecular markers. In addition, these three molecular markers were highly sensitive to detecting C. fructicola using DNA extracted from the inoculated leaves of oil-tea Camellia. These findings enable us to rapidly and uniquely detect the Camellia anthracnose disease caused by Colletotrichum fructicola, which will equip farmers with an effective tool for monitoring Camellia anthracnose disease in the field and taking timely control measurements in advance.